Los organizadores gráficos del conocimiento (telarañas, metaplan y mapa de ideas) y su relación con el rendimiento académico en el área de ciencia y ambiente, de los niños/as de 4to y 5to de primaria de la I.E José Carlos Mariátegui - Reyna Mendoza, Mariela (2012)
The research entitled "Knowledge Graphic Organizers ( cobwebs, goal and plan map of ideas) and its relationship to academic achievement in Science and Environment area of children's fourth and fifth graders of School Experimental" José Carlos Mariátegui "arase because of a concern to understand the relationships that exist between the organizers and academic performance, despite difficult problems that currently exist. To do this we formulate the following objectives, General was to determine the relationship between the use of graphic organizers Knowledge (Cobwebs, Meta plan and map ideas) and Student Achievement in the Field of Science and Environment of children and girls in fourth and fifth grade of School Experimental José Carlos Mariátegui of the Faculty of Humanities and Education-Rioja, and analyze specific Achievement in the Field of Science and Environment, analyze the use of the Organizers of Knowledge (Cobwebs, Meta plan and map ideas) in teaching and establish the relationship between the organizers of Knowledge and Student Achievement. The theoretical assumptions were supported by Serafini, Mary (1994 ), Bladimiro Soto (2000), Castilian (1999) and consisted hypothesis whose direct relationship exists between the use of graphic organizers Knowledge (Cobwebs, Meta plan and map ideas) and academic performance in the area of Science and Environment of the children of the fourth and fifth graders of School Experimental José Carlos Mariátegui of the Faculty of Humanities and Education-Rioja, 201 O, which passed with a confidence of 95%, the same as is shown by the line graph and the value obtained from the Pearson correlation coefficient to be a very strong positive correlation is explained by the 75.39% of the population.